2009
DOI: 10.1158/0008-5472.can-09-0729
|View full text |Cite
|
Sign up to set email alerts
|

p27Kip1 Stabilization Is Essential for the Maintenance of Cell Cycle Arrest in Response to DNA Damage

Abstract: One of the current models of cancer proposes that oncogenes activate a DNA damage response (DDR), which would limit the growth of the tumor in its earliest stages. In this context, and in contrast to studies focused on the acute responses to a one-time genotoxic insult, understanding how cells respond to a persistent source of DNA damage might become critical for future studies in the field. We here report the discovery of a novel damage-responsive pathway, which involves p27 Kip1 and retinoblastoma tumor supp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 30 publications
3
57
0
1
Order By: Relevance
“…Hence, repression of the CDKs by miR-182-5p would lead to activation of RB and a cell cycle arrest, enabling efficient DNA repair. The second class is the components of the SCF complex that are responsible for the ubiquitylation of several proteins that are essential for the DDR, e.g., SKP1 and 2, components of the SCF complex, which are known to degrade p27 KIP1 (CDKN1B), an essential mediator of cell cycle arrest in response to DNA damage (Cuadrado et al 2009). Another component of the SCF complex, BTRC, is also known to ubiquitylate ATF4, which plays a role in maintaining genomic integrity (Lassot et al 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, repression of the CDKs by miR-182-5p would lead to activation of RB and a cell cycle arrest, enabling efficient DNA repair. The second class is the components of the SCF complex that are responsible for the ubiquitylation of several proteins that are essential for the DDR, e.g., SKP1 and 2, components of the SCF complex, which are known to degrade p27 KIP1 (CDKN1B), an essential mediator of cell cycle arrest in response to DNA damage (Cuadrado et al 2009). Another component of the SCF complex, BTRC, is also known to ubiquitylate ATF4, which plays a role in maintaining genomic integrity (Lassot et al 2001).…”
Section: Resultsmentioning
confidence: 99%
“…These phenotypes are completely rescued in double Skp2 -/-p27 -/-mice, indicating that the accumulation of p27 in S, G 2 , and M phases in Skp2 -/-cells is responsible for a failure to progress to mitosis, resulting in polyploidy (20,21). Recently, several groups reported that ionizing radiation or DNAdamaging drugs could induce p27 expression to trigger an arrest in G 2 /M and that in the absence of p27, cells failed to undergo cell cycle arrest (22)(23)(24). Moreover, the loss of p27 was associated with increased chromosomal instability in response to DNA damage, as cells could proceed through mitosis with unrepaired DNA (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several groups reported that ionizing radiation or DNAdamaging drugs could induce p27 expression to trigger an arrest in G 2 /M and that in the absence of p27, cells failed to undergo cell cycle arrest (22)(23)(24). Moreover, the loss of p27 was associated with increased chromosomal instability in response to DNA damage, as cells could proceed through mitosis with unrepaired DNA (22)(23)(24). In addition, p27 deficiency impeded Rad51-mediated DNA repair due to increased CDK1-mediated phosphorylation of BRCA2, which inhibits the BRCA2-Rad51 interaction and Rad51-mediated repair (22).…”
Section: Introductionmentioning
confidence: 99%
“…Some reports suggest that the induction of p27/kip1 by DNA damage is unaltered (Vikhanskaya et al, 1996;Balasubramanian et al, 1999;Vivo et al, 2003), but others have observed increases in p27/kip1 increment (Zhou et al, 2004;He et al, 2006;Cuadrado et al, 2009).…”
Section: Discussionmentioning
confidence: 99%